"But I Am Confident: God Will Not Leave Us This Way": From Slavery to Post-Slavery in Nouakchott's bidonvilles, Mauritania. (4th May 2021) - McDougall, E. Ann
ABSTRACT: This article analyzes the urban growth of Nouakchott, capital of Mauritania, between 1960 and 2016. Growth was shaped both by in-migration driven by recurrent droughts, and by the end and subsequent transformation of slavery. Living in Nouakchott's poor, unplanned bidonville neighborhoods influenced how slaves and slave descendants saw themselves, especially in relation to former masters. Some joined impoverished but non-servile cultivators and herders working in the informal economy. Others used Islam to claim their former masters' continuing protection. Still others used the urban environment to negotiate new social roles and relationships. Since the 1990s, bidonville life has also shaped how hundreds of thousands of voters expressed themselves at the ballot box. In 2007, this power extended to electing the President himself. This history illuminates how the intertwined transformations of Nouakchott as an urban living space and slavery as a social institution explain Mauritania's contemporary "post-slave" identity, tensions, and political volatility.